Method for coating a metal substrate

JP2025534476A5Pending Publication Date: 2026-10-16GMD METAL COATING BV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025520669
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-10-10
Filing Date
2023-10-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

Existing corrosion-resistant coatings for metal substrates are inefficient in application and curing processes, and there is a need for coatings that provide good corrosion resistance while allowing easy spraying and curing under mild conditions.

Method used

A coating composition comprising metal particles (20-120 microns, 50-95% by weight), a curable resin (5-50% by weight), and a catalyst, applied and cured to achieve a 50-2000 micron thick layer, which can be easily sprayed and cured under mild conditions, providing excellent adhesion, wear resistance, and corrosion resistance.

Benefits of technology

The coating achieves long-lasting, flexible, and attractive coatings with improved adhesion and corrosion resistance, suitable for outdoor use, even on vertical surfaces, with a lifespan of up to 60 years and easy application on large objects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for coating a substrate, the method comprising the steps of applying a layer of a coating composition to the substrate and curing the coating composition; where: the substrate is a metal substrate, The coating composition comprises: metal particles having an average diameter in the range of 20 to 120 microns in an amount of 50 to 95% by weight calculated on the total weight of the coating composition; a curable resin in an amount of 5 to 50 wt. % calculated on the total weight of the coating composition, wherein the curable resin is selected from the group consisting of epoxy resins, acrylic resins, and polyester resins; a catalyst suitable for promoting the curing of the curable resin; Including, The method according to claim 1, wherein the coating layer after curing has a total thickness of 50 to 2000 microns. The present invention also relates to a substrate provided with a coating layer. It has been found that when a metal substrate is coated with the above-described composition, a coating having excellent adhesion, abrasion, and corrosion resistance properties is obtained. In addition, the coating provides an attractive appearance. The coating can be easily applied by spraying and can be cured under relatively mild conditions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for coating a metal substrate, in particular to a method for coating a metal substrate with a coating that improves the corrosion resistance of the metal substrate, and also to a metal substrate provided with a coating. [Background technology]

[0002] Corrosion-resistant coatings for metal substrates are known in the art. However, a need remains for corrosion-resistant coatings for metal substrates. In particular, there is a need for coating compositions that produce coatings that have good corrosion resistance, while allowing the coatings to be easily applied by spraying and cured under relatively mild conditions. Summary of the Invention [Means for solving the problem]

[0003] The present invention relates to a method for coating a substrate, the method comprising the steps of applying a layer of a coating composition to the substrate and curing the coating composition; where: the substrate is a metal substrate, The coating composition comprises: metal particles having an average diameter in the range of 20 to 120 microns in an amount of 50 to 95% by weight calculated on the total weight of the coating composition; a curable resin in an amount of 5 to 50 wt. %, calculated on the total weight of the coating composition, wherein the curable resin is selected from the group consisting of epoxy resins, acrylic resins, and polyester resins; a catalyst suitable for accelerating the curing of the curable resin; Including, The coating layer after curing has a total thickness of 50 to 2000 microns. The above method is provided.

[0004] It has been found that when a metal substrate is coated with the above-described composition, a film having excellent adhesion, wear, and corrosion resistance properties is obtained. The coating has a long life and is relatively flexible. In addition, the coating provides an attractive appearance. The coating can be easily applied by spraying and can be cured under relatively mild conditions. DETAILED DESCRIPTION OF THE INVENTION

[0005] The present invention and its associated advantages are further described below.

[0006] The coating composition comprises metal particles. The metal particles can be any known metal. The metal particles are selected from the group consisting of aluminum, zinc, tin, magnesium, and combinations thereof, and optionally alloys thereof. The use of aluminum and / or zinc is particularly preferred.

[0007] It is particularly preferred that at least 50% by weight, particularly at least 70% by weight, more particularly at least 80% by weight, and preferably at least 90% by weight of the total metal particles are aluminum particles. In one embodiment, all metal particles are aluminum particles. Aluminum has a lower density than zinc, imparting a lower weight to the coating for a given thickness. Furthermore, coatings with aluminum particles appear to be easier to spray onto vertical surfaces in thick layers, for example up to 500 microns, without intermediate drying, and without the coating running or sagging than coatings with zinc particles. Furthermore, the lifespan of coatings with aluminum particles appears to be longer than that of coatings with zinc particles. An aluminum particle-based coating applied in a single layer with a wet thickness of 500 microns and a dry thickness of 450 microns has a theoretical lifespan of 60 years.

[0008] An additional advantage of using aluminum particles is that the coating composition in the pot is less likely to sag than when zinc particles are used. This means that the "pot life" of the coating composition is longer. Coatings with aluminum particles have also been shown to have high flexibility. This not only means that the coating layer is more resistant to impacts, bending, and dents, but also means that the coated sheet can be further processed by bending and even rolling without damaging the coating layer.

[0009] The metal particles have an average diameter in the range of 20 to 120 microns. The average diameter is the D50, i.e., the value at which 50% of the particles have a larger diameter and 50% have a smaller diameter. Particle size distribution is conventional in the art and is determined, for example, through laser diffraction. If the particles are too large, the coating layer will be less uniform, thus reducing the coverage of the substrate. If the particles are too small, it will be difficult to obtain a layer of sufficient thickness and uniformity.

[0010] Preferably, the metal particles have an average diameter in the range of from 20 to 100 microns, more preferably from 30 to 90 microns, and even more preferably from 40 to 80 microns. Suitable metal particles are commercially available.

[0011] The metal particles are present in the coating composition in an amount of 50 to 95% by weight, calculated on the total weight of the coating composition before application to the substrate (ie, before curing).

[0012] One of the advantages of the present invention is that the coating composition has a relatively high metal content, and therefore the final coating layer contains a large amount of metal. This contributes to the composition's good corrosion resistance. Therefore, it may be preferable for the composition to contain at least 60% by weight, preferably at least 65% by weight, and in some cases at least 70% by weight of metal. Meanwhile, sufficient space is required for the resin, catalyst, and any additional components. Therefore, the amount of metal particles is 95% by weight or less, and it may be desirable for the composition to contain 90% by weight or less of metal particles, or 85% by weight or less of metal particles.

[0013] The exact amount of metal particles will also depend on the particle size and further properties of the metal particles, and in some cases, particularly when the metal is aluminum or when particles having an average particle size of more than 55 microns are used, it may be preferred for the composition to comprise 50 to 80 wt. %, especially 50 to 70 wt. %, of metal particles.

[0014] The composition comprises a curable resin selected from the group consisting of epoxy resins, acrylic resins, and polyester resins. Polyester resins are preferred. Thermosetting resins are preferred. It is particularly preferred that the resin is curable at temperatures of 100°C or less, particularly 60°C or less, more particularly 45°C or less, or 40°C or less. Suitable resin compositions are well known and do not require further explanation. The presence of curable resins other than those mentioned is neither necessary nor desirable. Therefore, in one embodiment, the coating composition does not contain more than 10% by weight, particularly not more than 5% by weight, of curable resins other than those specified above.

[0015] The resin is present in an amount of 5 to 50% by weight, calculated on the amount of the coating composition. If the resin is present in an amount less than 5% by weight, sufficient bonding is not obtained. If the resin is present in an amount of 50% by weight, there is insufficient space for the other components of the composition, especially the metal particles. It is preferred that the resin be present in an amount of 5 to 40% by weight, especially 5 to 30% by weight, and even more especially 5 to 25% by weight, calculated as resin polymer, based on the total weight of the composition.

[0016] The composition also includes a catalyst. The catalyst is selected to match the curing mechanism of the resin. Catalysts for thermosetting resins are preferred. Suitable catalysts are known and require no further explanation. The catalyst is applied in conventional amounts known in the art, generally in the range of 0.001 to 2 wt. %, calculated on the weight of the coating composition.

[0017] The coating composition may contain an organic diluent, for example, in an amount of 2 to 40% by weight calculated on the total coating composition. This is often desirable to give the composition good processing properties, especially a sufficiently low viscosity. Using less than 2% by weight of diluent usually does not achieve the effect of the diluent. Using more than 40% by weight of diluent detracts from the amounts of other components. It may be attractive to use at least 5% by weight of diluent and / or not more than 35% by weight, more preferably not more than 30% by weight.

[0018] Suitable diluents include organic diluents such as alcohols having 2 to 10 carbon atoms, e.g., ethanol, propanol, butanol, and octanol. Other suitable diluents include alkyl esters and alkyl ethers, e.g., methyl acetate, ethyl acetate, methyl ethyl ketone, and methyl isobutyl ketone, and alkyl ethers of glycols. Aromatic hydrocarbons such as benzene, toluene, and xylene, as well as mixtures of petroleum-derived aromatic solvents, can also be used.

[0019] Preferably, the coating composition comprises 5 to 40 wt. % of a diluent having a boiling or decomposition point above 60° C., preferably above 80° C. Compared to low-boiling solvents, such as ethanol, this has the advantage that the diluent remains in the composition for a long time, thereby maintaining good workability. The ranges mentioned above for the total amount of diluent also apply here.

[0020] One particularly preferred class of diluents is synthetic oils and natural oils. Suitable natural oils include vegetable oils such as cottonseed oil, peanut oil, coconut oil, cocoa butter, pumpkin seed oil, linseed oil, corn oil, olive oil, palm kernel oil, palm oil, rapeseed oil, sesame oil, soybean oil, sunflower oil, grape seed oil, walnut oil, and wheat germ oil. Animal oils, such as fish oils, can also be used, as can oils from algae. Suitable oils also include petroleum products, such as petroleum fractions, for example, in the range of 50 to 400°C, particularly 50 to 250°C. Suitable petroleum fractions include gasoline, diesel, and kerosene.

[0021] The use of vegetable oils is preferred as they are durable and provide good results. It is preferred to use peanut oil, linseed oil, corn oil, olive oil, palm oil, rapeseed oil, sunflower oil, sesame oil or soybean oil.

[0022] Mixtures of different diluents and / or different oils can be used. Preferably, the composition comprises a total of 5 to 40% by weight of synthetic and / or natural oils, in particular vegetable oils as indicated above. The ranges given above for the total amount of diluent also apply here.

[0023] It is also preferred that at least 30% by weight, more preferably at least 50% by weight, even more preferably at least 60% by weight, or at least 70% by weight, or at least 80% by weight of the total amount of diluent in the composition is a synthetic or natural oil, especially a vegetable oil, as set out above.

[0024] Because the metal content of the coating is important to efficacy, and the inclusion of solid particles other than metal particles can adversely affect the workability and efficacy of the composition, it is preferred that at least 80 wt. %, particularly at least 90 wt. %, even more particularly at least 95 wt. %, or at least 98 wt. % of the solid particles in the composition consist of metal particles having an average diameter in the range of 20 to 120 microns.

[0025] The use of glass particles in coating compositions has been described in the literature. Their presence is neither necessary nor desirable in the case of the composition according to the present invention. The presence of glass particles occupies the volume occupied by metal particles in the coating composition according to the present invention. Therefore, it is preferred that the composition contains no more than 7% by weight, preferably no more than 5% by weight, more preferably no more than 2% by weight, and particularly preferably no more than 1% by weight of glass particles.

[0026] In one embodiment, the sum of the metal particles, resin, catalyst, and diluent forms at least 70 wt.%, particularly at least 80 wt.%, more particularly at least 90 wt.%, and particularly at least 95 wt.% of the coating composition.

[0027] The substrate to be coated by the method according to the present invention is a metal substrate, generally a steel substrate. Since the method according to the present invention is intended to provide corrosion resistance, the substrate is often intended for outdoor use or use in a humid environment. Suitable substrates include, for example, machines and machine parts; mechanical structural parts for other infrastructures (e.g., buildings, roads, and wind turbines); and industrial-scale substrates selected from the group consisting of other offshore and onshore applications. The substrate may be provided with a primer, but this is not required. In one embodiment, the coating composition is applied directly onto the metal substrate without the presence of an intermediate layer.

[0028] The coating composition can be applied by conventional methods, such as spraying, rolling, pouring, ironing, and dipping. Application by spraying is preferred because it is a fast and accurate method for applying the coating composition, which produces uniform results. Airless spraying is particularly preferred because it is a known method for spraying large areas. It has been found that the composition according to the present invention can be handled well by spraying, especially airless spraying.

[0029] The coating composition may be applied in one or more layers, for example, two, three, four, or five layers. A single layer, as used herein, is a layer applied without intermediate curing. If the composition is applied in more layers, the composition must be at least partially cured between layers. Depending on the curing mechanism, this can be easily achieved. A feature of the present invention is that the coating composition can be applied to a relatively high total layer thickness without intermediate curing. This is particularly true for aluminum-based coatings.

[0030] After application of the composition, a curing step is carried out. How the curing step is carried out depends on the curing mechanism of the resin used. Thermal curing is preferred. In this case, the curing is preferably carried out at a temperature of 5 to 100°C, in particular 10 to 60°C, more in particular 15 to 45°C, for example 20 to 40°C. The time required depends on the selected temperature (the lower the temperature, the more time is required). The curing time generally takes 1 to 48 hours, more in particular 2 to 36 hours, for example 4 to 30 hours. At lower temperatures, the curing time will be longer than at higher temperatures.

[0031] After curing, the composition has a total layer thickness of 50 to 2000 microns. This is the sum of all applied layers. A layer thickness of less than 50 microns does not achieve the desired anti-corrosion effect. A layer thickness of more than 2000 microns often does not provide additional benefits. The total layer thickness is preferably at least 75 microns, more preferably at least 100 microns, and especially more than 150 microns. The total layer thickness is preferably 1500 microns or less, more preferably 1200 microns or less. The coating thickness to be selected depends on the desired lifespan of the coating layer. In some cases, a layer thickness of 1000 microns or less, 800 microns or less, 600 microns or less, or 400 microns or less may be sufficient. It has been found that the coating layer according to the present invention provides sufficient protection even in relatively thin layers.

[0032] After application and curing, one or more post-treatment steps may be optionally carried out. Suitable finishing steps include sanding or polishing to obtain a surface with a metallic appearance. If desired, one or more further coating layers can be applied, but this is not essential. The further coating layers will generally serve a decorative purpose, for example, to provide a desired color. The coating layers obtained according to the present invention can be directly colored.

[0033] The present invention also provides a metal substrate having a coating layer containing metal particles and a resin, the layer comprising a coating composition, The coating composition comprises: metal particles having an average diameter in the range of 20 to 120 microns in an amount of 50 to 95% by weight calculated on the total weight of the coating composition; a resin in an amount of 10 to 50 wt. % calculated on the total weight of the coating composition, wherein the resin is selected from the group consisting of epoxy resins, acrylic resins, and polyester resins; A catalyst suitable for accelerating the curing of resins Including, The coating has a total thickness of 50 to 2000 microns. Regarding the above metal substrate.

[0034] The preferred aspects expressed above regarding the nature of the substrate, the coating composition, layer thickness and other features also apply to this embodiment of the invention. Preferably, the layer of the coating composition is cured.

[0035] It will be apparent that preferred embodiments described for different aspects of the invention may be combined unless they are mutually exclusive.

[0036] The present invention is illustrated by, but not limited to, the following examples.

[0037] Example 1: Compositions tested

[0038] Coating A: Coating composition containing zinc particles

[0039] A coating composition containing zinc particles was prepared by mixing zinc particles with a curable polyester resin and a diluent. The composition also contained a catalyst. The zinc particles had an average particle size of 45 microns. The coating composition contained 72% by weight of zinc particles. The diluent was vegetable oil and was applied in an amount of approximately 7% by weight, calculated on the total coating composition. This coating composition is also referred to herein as a zinc coating.

[0040] Coating B: Coating composition containing aluminum particles

[0041] A coating composition containing aluminum particles was prepared by mixing aluminum particles with a curable polyester coating and a diluent. The composition also contained a catalyst. The aluminum particles had an average particle size of 45 microns. The coating composition contained 55% by weight of aluminum particles. The diluent was vegetable oil and was applied in an amount of approximately 11% by weight, calculated on the total coating composition. This coating composition is also referred to herein as an aluminum zinc coating.

[0042] Example 2: Coating on a metal substrate and properties of the coating

[0043] A steel panel was coated with the aluminum coating and the zinc coating from Example 1. The coatings were applied by airless spraying. The coatings were cured at a temperature of 20° C. for approximately 24 hours.

[0044] For the zinc coating, the thickness after curing was about 500 microns. For the aluminum coating, the thickness after curing was about 850 microns.

[0045] Example 3: Testing of the coating obtained in Example 2

[0046] Neutral salt spray test according to ISO 12944-6 C5H

[0047] A number of aluminum-coated and zinc-coated samples were subjected to a neutral salt spray test according to ISO 12944-6 C5H. The test lasted approximately 1440 hours. The temperature was 35±2°C. The brine contained 5% NaCl. The pH of the salt solution was 6.5-7.2. The liquid volume was 80 cm per hour. 2 For a 100% zinc coating, ISO 12944 equates salt spray testing to 15-20 years of exposure.

[0048] Pull-off adhesion

[0049] Peel adhesion was measured on various samples before and after salt spray testing, with the average values ​​being as follows:

[0050] [Table 1]

[0051] A value of 5 MPa is sufficient to pass the test according to ISO 12944-6 C5H, indicating that both coatings have excellent peel adhesion before and after the salt spray test.

[0052] Wear test

[0053] The abrasion of the coating layers was investigated according to ASTM D4060:2014 (Taber Abrasion) using a 1 kg load and an abrasion wheel CS 17 for 1000 cycles. The panel with zinc coating A showed an abrasion index of 0.10. The panel with aluminum coating B showed an abrasion index of 0.16.

[0054] Layer thickness

[0055] Cross sections were made to examine the structure of the coating layer. The layer thickness was measured. This was done both before and after the salt spray test. In each case, the thickness was determined at six points on the panel.

[0056] [Table 2]

[0057] [Table 3]

[0058] For both zinc coating A and aluminum coating B, the thickness of the coating layer before the salt spray test was greater than the thickness after the test. In the case of the zinc coating, the reduction in thickness was approximately 150 microns. ISO 12944 equates salt spray testing of 100% zinc coatings to 15-20 years of exposure. A reduction of 4.2-8.4 microns is acceptable for interior coatings in humid and aggressive industrial areas, coastal areas with high salinity, and areas with heavy condensation and pollution. A reduction of 150 microns over 20 years corresponds to 7.5 microns per year, and is therefore a good result.

[0059] In the case of the aluminum coating, the reduction in thickness was about 160 microns, which is also a good result.

[0060] Example 4: Durability Test - Aluminum Coating - 6 Months

[0061] A primer-coated carbon steel sheet was partially coated with the coating layer described as Coating B in Example 1 and cured under ambient conditions. The coating had a cured thickness of approximately 150 microns. The coated sheet was exposed to outdoor weather conditions (Westervoort, the Netherlands) for 18 months. After 18 months, the corrosion rating was approximately the same as that of the sheet immediately after coating application. Adhesion testing by X-cut according to ASTM-D3359-09 (for coatings thicker than 125 microns) yielded a rating of 4A. This example demonstrates that the coating has excellent durability.

[0062] Example 5: Adhesion to Blasted Panels

[0063] Metal substrates are typically blasted before coating to improve adhesion. It is preferable to apply the coating as soon as possible after blasting, typically within six hours. This is not always possible in practice. Therefore, the effect of prolonged storage of metal sheets after blasting and before coating on coating adhesion was investigated.

[0064] Steel panels were blasted to an SA of 2.5 according to ISO 8501-1. The panels were then stored outdoors, and after the time indicated in the table below, a layer of the coating described as Coating B in Example 1 was applied and then dried at ambient temperature. The coating was applied with a roller. After drying, adhesion was determined according to ISO 4624:2016. A value of 5 or greater is an acceptable result.

[0065] [Table 4]

[0066] Test results showed that the coating had good adhesion even when it was not applied to the metal sheet immediately after blasting, which allows for greater flexibility in application.

[0067] Example 6: Adhesion to other coating layers

[0068] The coating layer according to the present invention may be provided with further coating layers, for example to achieve desired color or surface properties. It is important that any further coating layers exhibit good adhesion to the coating of the present invention. This adhesion has therefore been investigated for a variety of commercially available coatings.

[0069] After the steel pipe was blasted to SA 2.5, it was coated by airless spray with the coating composition described as Coating B in Example 1 at an average layer thickness of 174 microns and then air dried. The coating had an adhesion of 10.71 MPa and 13.36 MPa according to ISO 4624:2016 (2 dollies).

[0070] The pipes were then coated with various commercially available coating compounds by airless spraying. The table below shows the results of the adhesion test according to ISO 4624:2016.

[0071] [Table 5]

[0072] It is clear that all compositions tested exhibited satisfactory adhesion.

[0073] Example 7: Effect of rolling on coated sheets

[0074] Four steel plates measuring 1000 x 550 x 8 mm were blasted with coating B from Example 1 and coating B from Example 4, and then coated to an average layer thickness of 120 microns after drying.

[0075] Two plates were first rolled onto a 3-meter diameter drum and then welded together. Two other plates were first welded and then rolled onto a 3-meter diameter drum. In both cases, the rolling bending did not result in damage to the coating. In the case of welding, it did result in damage to the coating directly below the weld. This damage was easily removed by sanding.

[0076] Example 8: Applying coatings to large objects

[0077] Coating B from Example 1 was applied to a section of a steel bridge. The bridge section had a total coated area of ​​88 m 2 The bridge section was coated on all sides (top, bottom, and sides). Application was by airless spraying in two layers without intermediate drying. The final coating thickness was 150 microns. It was found that the coating according to the invention is easy to apply even to large objects, vertical surfaces, and surfaces that must be sprayed upwards. The coating layer was uniform and of good quality.

Claims

1. A method for coating a substrate, comprising the steps of applying a layer of a coating composition to the substrate and curing the coating composition, Here, The aforementioned substrate is a metal substrate, The coating composition is The coating composition comprises, in an amount of 50 to 95% by weight, metal particles having an average diameter D50 determined by laser diffraction, in the range of 20 to 120 microns, wherein at least 50% by weight of the metal particles are aluminum particles. The coating composition comprises a curable resin in an amount of 5 to 50% by weight, calculated from the total weight, wherein the curable resin is selected from the group consisting of epoxy resin, acrylic resin, and polyester resin. A catalyst suitable for promoting the curing of the aforementioned curable resin and Includes, The cured coating layer has a total thickness of 50 to 2000 microns. The aforementioned method.

2. The method according to claim 1, wherein the curable resin is an acrylic resin or a polyester resin.

3. The method according to claim 3, wherein at least 70% by weight of the metal particles are aluminum particles.

4. The method according to claim 1 or 2, wherein the metal particles have an average diameter D50 determined by laser diffraction, in the range of 20 to 100 microns.

5. The method according to claim 1 or 2, wherein the coating composition contains metal particles in an amount of 60 to 95% by weight, calculated by weight of the total weight of the coating composition.

6. The method according to claim 1 or 2, wherein the particles have an average particle size of more than 50 microns, and / or the coating composition contains the metal particles in an amount of 50 to 80% by weight.

7. The method according to claim 1 or 2, wherein the resin is a resin that can be cured at a temperature of 100°C or lower.

8. The method according to claim 1 or 2, wherein the resin is present in an amount of 5 to 40% by weight as a resin polymer relative to the total weight of the composition.

9. The method according to claim 1 or 2, wherein the coating composition contains an organic diluent in an amount of 2 to 40% by weight.

10. The method according to claim 9, wherein the diluent is selected from synthetic oils or natural oils.

11. The method according to claim 1 or 2, wherein the substrate is a metal substrate intended for outdoor use or use in high humidity environments, wherein the substrate is selected from the group of metal structural components for machinery and machine parts; buildings, roads, and other infrastructure including bridges, factories and wind turbines.

12. The method according to claim 1 or 2, wherein the coating composition is applied by spraying.

13. The method according to claim 1 or 2, wherein the coating composition is cured at a temperature of 5 to 100°C.

14. A metal substrate having a coating layer containing metal particles and resin, wherein the layer is made of a coating composition. The coating composition is The coating composition comprises, in an amount of 50 to 95% by weight, metal particles having an average diameter D50 determined by laser diffraction, in the range of 20 to 120 microns, wherein at least 50% by weight of the metal particles are aluminum particles. The coating composition contains a resin in an amount of 10 to 50% by weight, calculated from the total weight, wherein the resin is selected from the group consisting of epoxy resin, acrylic resin, and polyester resin. A catalyst suitable for accelerating the curing of resins and Includes, The coating has a total layer thickness of 50 to 2000 microns determined after curing. The aforementioned metal substrate.